2009
DOI: 10.1177/1363459308101808
|View full text |Cite
|
Sign up to set email alerts
|

Whose body is it anyway? Verbalization, embodiment, and the creation of narratives

Abstract: This article examines the creation of narratives between people with severe disabilities and the personnel working with them. It shows that although a co-created narrative of what it means to be severely disabled (the story of dependence) seems to prevail, another narrative (the story of autonomy) is also told, where the story of dependence is rejected by the person with disabilities. However, this story of autonomy only becomes clear if we recognize three central claims: (1) there is a connection between wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Due to the motor limitations, most people with PIMD are unable to move independently, and they are therefore dependent on other actors in their environment, such as direct support persons (DSPs), to be positioned in such a way that it is possible to make contact. Antelius (2009) argued that positioning is related to what an individual is allowed or able to do: sitting within reach of somebody enables the individual with PIMD to touch the other person and make contact, whereas sitting alone in a room or being further away from others limits all forms of contact for most of these people. Nijs et al (2015) found a relationship between the positioning of children with PIMD and peer-related behaviour.…”
mentioning
confidence: 99%
“…Due to the motor limitations, most people with PIMD are unable to move independently, and they are therefore dependent on other actors in their environment, such as direct support persons (DSPs), to be positioned in such a way that it is possible to make contact. Antelius (2009) argued that positioning is related to what an individual is allowed or able to do: sitting within reach of somebody enables the individual with PIMD to touch the other person and make contact, whereas sitting alone in a room or being further away from others limits all forms of contact for most of these people. Nijs et al (2015) found a relationship between the positioning of children with PIMD and peer-related behaviour.…”
mentioning
confidence: 99%
“…The presented empirical example illustrates recognizable challenges in rehabilitation practice. Studies claim that ongoing rehabilitation practice is inadequately tailored to the rehabilitation needs of individual patients and the complexities involved in intensive neurorehabilitation are not consistently addressed (Antelius 2009;Mattingly 2006;Pryor and O'Connel 2009;van den Broek 2005). Situated learning theory contributes by visualizing that the pedagogic challenge in neurorehabilitation is twofold: It encompasses creating a learning environment to facilitate the patient in gaining or compensating for changed functional abilities to participate as well as assisting the patient to learn or compensate for changed everyday life competencies (Lave and Wenger 1991;Lave and Wenger 2005;Wenger 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Despite all efforts, patients commonly reach varying outcomes (van den Broek 2005). This may be explained by the severity of the injury, but another possible contributing factor is that the current rehabilitation practice is inadequately adjusted to the need of the individual patient (Antelius 2009;Mattingly 2006;Pryor and O'Connel 2009;van den Broek 2005). and skills to handle everyday life after the TBI, but the community of practice is directed towards facilitating the learning process for the newcomer.…”
Section: Introductionmentioning
confidence: 99%
“…Moffatt and Mackintosh 2009 , in which the interpretation process is described in detail but the researchers themselves are not; and Doshani et al 2007 who describe the researcher as linguistically matched, with no further information). Authors suggest that such minimal information potentially results in interviewer anonymity and misplaced assumptions of neutrality (Antelius 2009 ; Brown and Boardman 2011 ; Dunbar, Rodriguez and Park 2002 ; Sharma, Reimer-Kirkham and Cochrane 2009 ). Indeed, in the field of cross-ethnic research, authors suggest that the ascribed and interpretable ethnicity of the researcher becomes hidden behind the focus on the participant (Ellingson 2006 ; Torres 2009 ; R. Willis 2012 ).…”
Section: Introductionmentioning
confidence: 99%